Ethical veganism as a belief and its posible repercussions in the Spanish labour law - Jover Ramírez, Carmen (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The study presented here takes as its starting point “ethical veganism” as a belief. In the light of the British case Casamitjana, it reflects on the different consequences that its interference could have in the sphere of the employment relationship. From its consideration as a possible cause of discrimination to its interrelation with the employer’s powers, the aim is to offer a vision of this new reality, proposing possible solutions and responses from the plural and multicultural vision that, already evident in a large part of the economic, social, cultural, etc., spheres of society, has also come to settle in the heart of the labour relationship that links employee and employer.
Keywords: ethical veganism; belief; freedom of thought; employment discrimination; employment relationship